Digital Sexual Harassment of Young Women in Mesuji Lampung: Mubadalah Analysis - M. Anwar Fauzi; Ahmad Failasuf Nasuha (Journal of Islamic Mubadalah, 2025)
Digital sexual harassment is increasingly becoming a real threat to adolescent girls in the era of social media, including in areas that are less accessible to protection systems, such as Mesuji Regency, Lampung. This phenomenon shows that digital space is not yet completely safe, especially for vulnerable groups with minimal gender and digital literacy. This study aims to answer two main questions: (1) what are the forms of digital sexual harassment experienced by adolescent girls in Mesuji, and (2) how the Mubadalah concept can be used as an alternative solution to deal with this problem. The study was conducted using a qualitative approach collected through observation, in-depth interviews, and documentation of two adolescent girls in Masuji, then analyzed through data reduction, data display, and conclusions/verification. The results of the study showed that respondents experienced various forms of digital violence, such as explicit sexual comments, vulgar messages, to body shaming, which causes serious psychological impacts. Whereas, low digital literacy and strong social stigma are inhibiting factors for victims to report. In this context, the Mubadalah perspective is present as an Islamic interpretation approach that emphasizes gender justice and equality, and is relevant to building collective awareness in creating a safer and moreover equal digital space for adolescent girls.